FUZZY LOGIC APPLICATION IN IOT BASED DISEASE MONITORING SYSTEM FOR APPLE ORCHARDS IN HIMACHAL PRADESH - Karuna Sheel, Dr. Anil Sharma (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
IoT is a technology of interconnected computing devices and has a huge contribution now a days in the diverse application areas. Himachal Pradesh secured second largest place in India for apple cultivation. Apple cultivation is the fastest rising activity in the state. The economy of this state is predominantly dependent on apple cultivation. Apple is high in demand throughout the year. Fluctuation in climate and weather conditions have a huge impact on cultivation and quality of apple. The success of apple production highly depends on climatic and environmental factor like temperature and humidity. Monitoring of these environmental factors of an orchard can help to prevent the apple from diseases.The application ofFuzzy logic is able to define various states rather than two states. The present study is focusing to design an IoT based system using fuzzy logic application to predict the various diseases and their impact on the apple during the different whether conditions. For this, fuzzy logic application with some popular IoT boards, sensors, Wi-Fi transreceiver and an android based application will be used to monitor the data which can be evaluated for further recommendations.